Clinical and radiological feature of lymphoepithelial cyst of the pancreas - Terakawa, Hirofumi (World J Gastroenterol, 2014)
A lymphoepithelial cyst (LEC) of the pancreas is a rare benign lesion. Because patients with LEC of the pancreas have a good prognosis, it is important that these lesions are accurately differentiated from other more aggressive pancreatic neoplasms for an appropriate treatment strategy. Previous studies have reported that a definitive diagnosis of LEC often cannot be obtained based solely on the findings of preoperative imaging (e.g., Computed tomography or Magnetic resonance imaging). In this study, we reviewed four cases of pancreatic LECs to investigate the feature of LECs. We reviewed these cases with regard to symptoms, imaging findings, surgical procedures, and other clinical factors. We found that LEC was associated with unique characteristics on imaging findings. A preoperative diagnosis of LEC may be possible by comprehensively evaluating its clinical and imaging findings.